ADAPTASI BUDAYA PADA MAHASISWI NON-KMI DI UNIVERSITAS DARUSSALAM GONTOR: Studi Fenomenologi Pada Mahasiswi Non-KMI di UNIDA Gontor - Bella Oktafia; Diah Rukmini (Universitas Muhammadiyah Jember, 2025)
For students who choose to study away from home, it's not an easy decision, although there are risks such as not being able to adapt to a new culture, but the experience gained will definitely also be more, one of which can find out the culture of the place and friends from different regions. University of Darussalam Gontor is a university under the auspices of Pondok Modern Darussalam Gontor. In UNIDA there is a designation of KMI students for graduates from Gontor and there is a designation of Non-KMI (NK) students for students who graduated from other than KMI. Given that NK students who graduated from SMA/SMK/MA have never experienced life in an Islamic boarding school, there must be a lot of new things found, students' difficulties in adapting often cause depression and make them break many rules. This study aims to determine the strategies of NK students who graduated from SMA/SMK/MA in adapting to the culture in their new environment while studying at the pesantren higher education level at UNIDA Gontor. The method used in this research is phenomenology with interview and observation data collection techniques. In this study, cultural adaptation theory and accommodation theory were used. The results of this study are that most NK students who have passed several phases in cultural adaptation are still compromising and adapting to the environment and culture at UNIDA.